Evaluation of impact of fixed orthodontic treatment on salivary pH (Journal of Pharmaceutical Negative Results, 2023)
Background: The present study was undertaken for assessing the effect of fixed orthodontic treatment on salivary pH.Materials & methods: 25 patients undergoing fixed orthodontic treatment were enrolled. Clinical and radiographic details were also recorded separately. The pH values were measured with portable pH meter strips at the same four time points. Measurement of pH was done at baseline, 6 weeks post initiation of fixed orthodontic treatment, 12 weeks post initiation of fixed orthodontic treatment, and 18 weeks post initiation of fixed orthodontic treatment.Results: Mean pH at baseline, 6 weeks post initiation of fixed orthodontic treatment, 12 weeks post initiation of fixed orthodontic treatment, and 18 weeks post initiation of fixed orthodontic treatment was found to be 7.18, 6.62, 6.89 and 6.99 respectively. While analyzing statistically, significant results were obtained. Conclusion: During the course of fixed orthodontic treatment, there is a significant fall salivary pH.